Pengabdian Mahasiswa Dalam Program Praktek Lapang Tematik - Jubil Ezer Sihite; Mentari Telaumbanua; Monica Sinaga; Gita Simaremare; Agrioky Damanik (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2022)
Thematic Field Practice Activities are a learning process as well as a form of real work dedication for HKBP Nommensen students, Faculty of Language and Arts, English Literature and Music Arts Study Programs, especially in the field of education. This activity is aimed at fostering empathy and caring, and is expected to give birth to a strong, superior, noble personality, and can become an extraordinary person when he has entered the community, has a leadership spirit. The purpose of this activity is of course to further improve students' abilities in assessing and assessing any differences between theoretical material and practical material, thereby increasing the quality of students to solve a real problem. This is carried out based on mutual agreement in surveying each of the existing stages, and then based on discussions with the institutions/companies who are willing to make this activity run directly and also in accordance with the Certificate of Assignment that has been determined. Of course, this can be seen in students with real work in the ability to channel and provide good learning applications to every student at the HKBP Hutabaru Binjai Church.